6x-(5x+9)=5x-29

Simple and best practice solution for 6x-(5x+9)=5x-29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-(5x+9)=5x-29 equation:


Simplifying
6x + -1(5x + 9) = 5x + -29

Reorder the terms:
6x + -1(9 + 5x) = 5x + -29
6x + (9 * -1 + 5x * -1) = 5x + -29
6x + (-9 + -5x) = 5x + -29

Reorder the terms:
-9 + 6x + -5x = 5x + -29

Combine like terms: 6x + -5x = 1x
-9 + 1x = 5x + -29

Reorder the terms:
-9 + 1x = -29 + 5x

Solving
-9 + 1x = -29 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-9 + 1x + -5x = -29 + 5x + -5x

Combine like terms: 1x + -5x = -4x
-9 + -4x = -29 + 5x + -5x

Combine like terms: 5x + -5x = 0
-9 + -4x = -29 + 0
-9 + -4x = -29

Add '9' to each side of the equation.
-9 + 9 + -4x = -29 + 9

Combine like terms: -9 + 9 = 0
0 + -4x = -29 + 9
-4x = -29 + 9

Combine like terms: -29 + 9 = -20
-4x = -20

Divide each side by '-4'.
x = 5

Simplifying
x = 5

See similar equations:

| 7m-20=2m | | 110+35+x+12=180 | | 8-7r+7=1 | | -6(6x-8)+5=-36x+53 | | 3k+8-k=0 | | -3y+15=2y-10 | | x^2+57x-87=0 | | 4x=-1y+20 | | 49+90+x=180 | | y=-2x^2+x | | 4b+10(b-1)= | | 5y+4=20y-26 | | -4a+a=-12 | | 25l+36=85 | | 2x+22=x+14 | | z^2-24z+144=0 | | -4(-7x+5)=148 | | 5n-7-2=11 | | 1+2x-7=-4 | | 5x-45=2x-48 | | (8x^2+1)=(12x^2+6) | | 95+90+95+x=180 | | 8n+7n=-15 | | 7y+2x-10=0 | | -6(-1+3x)=-192 | | 8-n=3 | | 9(8x+1)+1=186+8(3x+2) | | 90+90+90+x=180 | | 1.66666666667v+4+0.33333333333v=8 | | 24+(5x-2)=-2(4x-4) | | 6g+1=37 | | 4x-4=4x-7 |

Equations solver categories